Visual Identity and Packaging Design for Bécik Bécik - Helena Calista; Brian Alvin Hananto (School of Design Universitas Pelita Harapan, 2022)
In association with the Indonesian Association of Graphic Designers (ADGI), Kemenparekraf organizes BEDA'KAN (Bedah Desain Kemasan) to encourage the growth of creative economic sectors in Indonesia. Throughout this enlightening activity, the authors had the opportunity to participate and be involved in designing a visual identity and packaging for Micro, Small, and Medium Enterprises (MSMEs) from Bali. Bécik Bécik has engaged in MSME in the craft sector since 1991 and is eager to grow and thrive in local and global markets. This design process is divided into three phases: pre-design, design, and post-design. These three phases guide the project's success in a systematic way to develop a representative brand identity. Hence, the design that can successfully represent the brand is then finalized and implemented in other media to present a powerful character of its identity.